Psychosocial impact on liver transplantation - Garcia, Clerison; Rotta, Ehideé La; Boin, Ilka de Fátima Ferreira; Garcia, Cássia; Lima, Agnaldo (Brazilian Journal of Transplantation, 2016)
In the last decades, studies have been made on the psychosocial impact and transplantation; however, it can be noticed that the researches assessing the psychosocial aspects or the psychosocial impact in the process of liver transplantation are scarce, especially among adults. Therefore, the purpose of this study was to present and discuss the findings in the literature regarding the psychosocial impacts of the liver transplantation. A review of the literature published between 2010 and 2016 in the databases Medline and Lilacs / Bireme and electronic sources Scielo and Google Scholar was conducted using as keywords: psychosocial impact, liver transplantation and psychology. Eleven articles were selected to meet the inclusion criteria, identifying eight articles that investigated the impact or psychosocial aspects in liver transplantation candidates or transplanted children and adolescents or their parents. Only three articles focused adult patients It can be concluded that studies assessing the psychosocial impact in adult patients affected with severe chronic hepatic diseases requiring liver transplantation and their relatives are few, and it is necessary to carry out studies with such aim, with the purpose to improve the psychological care of that group.